(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
In the first of the Charles Eliot Norton Lectures that he gave at Harvard in 1984, Frank Stella focused on “The necessity of creating pictorial space that is capable of dissolving its own perimeter and surface plane,” and claimed that “No one helped lighten this burden more than Caravaggio.” At a certain point in his talk, the American artist went so far as to say that Caravaggio anticipated the invention of the gyroscope, the technological device which makes the virtual experience possible. Stella’s lecture is the starting point for developing an anachronistic path through pictorial and digital media, in light of their ability to produce illusionistic effects on viewers. In particular, building on Michael Fried’s theory of art and image, this paper investigates virtual experience with reference to two different moments: the “immersive” moment, in which one has the impression of stepping into the frame, and the “specular” one, where the illusionistic effects are revealed; the attraction, when sinking into an image that has become an environment, and the distancing, when the image itself beckons to us and we are invited to reflect on our position as viewers.